Serological and Molecular Detection of Hepatitis B Virus and its Impact on Key Immunological Cytokines in Patients from Kirkuk, Iraq - Ahmed, Sara Hasan; Jafar, Nehan Bahaaldden (American Journal of Biology and Natural Sciences, 2026)
Introduction and Objectives: Hepatitis B virus (HBV) infection is a major global health burden, and a leading cause of liver-related mortality, including hepatocellular carcinoma and cirrhosis. HBV disrupts immune regulation and metabolic pathways, affecting NK and γδ T cells, IFN-γ, and TNF-α production. The current study aimed to isolate and identify HBV using PCR techniques and to evaluate specific immunological factors, including IL-10, TNF-α, IFN-γ, and SCF/MGF, comparing their levels between HBV patients and healthy controls. Materials and Methods: This study included 320 participants, 160 HBV patients and 160 healthy controls, recruited between January and July 2025 from Azadi Teaching Hospital, Gynecology, Obstetric and Pediatrics Hospital, Kirkuk Teaching Hospital, Al-Hawejah General Hospital, and private clinics in Kirkuk, Iraq. HBV infection was assessed using qualitative ELISA for HBsAg, anti-HBc, and anti-HBs, and quantitative real-time PCR. Cytokine levels were measured using sandwich ELISA kits. Results: HBV patients were older than controls (38.28 ± 11.32 vs. 34.80 ± 10.42 y; P < 0.05). All patients were ELISA-positive for HBV, while 41.88% were PCR-positive, indicating active viral replication; the remainder had suppressed or inactive infection. Cytokine analysis showed that VL+ patients had the highest IL-10 (84.1 pg/ml), TNFRAIL (735.27 pg/ml), IFN-γ (57.92 pg/ml), and CSF/MGF (147.28 pg/ml), significantly higher than Abs+ patients and controls (P < 0.05). Pearson correlation revealed a strong positive relationship between viral load and CSF/MGF (r = 0.5286) and a negative correlation with TNFRAIL (r = −0.265), while IL-10 and IFN-γ showed weak non-significant correlations. These findings indicate immune dysregulation in chronic HBV, with heightened inflammatory and anti-inflammatory cytokines, likely influenced by viral replication and systemic immune responses. Conclusions: HBV infection induces significant alterations in cytokine profiles, with elevated IL-10, TNFRAIL, IFN-γ, and CSF/MGF during active infection. Viral load closely associates with macrophage activation and immune dysregulation, highlighting its role in disease progression and chronic liver injury.